Pengembangan E-Modul Seni Rupa Menggunakan Model Project Based Learning Berbasis Aplikasi Canva di Kelas IV Sekolah Dasar - Yulva Fadillah; Mansurdin Mansurdin (Universitas Negeri Padang, 2025)
This research is motivated by the fact that in the learning process teachers only use package books provided at school, teachers have not used teaching materials that use technology. This research aims to develop an e-module using a canva-based Project Based Learning (PjBL) model in FINE ARTS learning in grade IV elementary school that is valid and practical. This type of research is R&D (Research and Development) development research. The steps to develop Canva-based learning media using the ADDIE model are the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The data collection instrument uses the e-module validation instrument and the e-module practicality instrument. The data analysis techniques in this study are the validity of the e-module and the practicality of the e-module. The results of the study show that the development of e-modules using the Canva Application-based Project Based Learning model in Fine Arts learning in grade IV SDN 18 Kampung Baru Padang